A review of forecasting studies for the restaurant industry: Focusing on results, contributions and limitations - Jeong-gil Choi; Yi-Wei Zhang; Nurulain Izzati Binti Mohd Nadzri (Global Business & Finance Review (GBFR), 2022)
Purpose: The purpose of this study is to explore restaurant forecasting studies through a comprehensive review of existing studies, discuss the contributions and limitations of those studies and uncover possible directions for future research. Design/methodology/approach: Key restaurant forecasting studies were collected by searching keywords in Google Scholar and selected based on their citation times. A final pool of 29 key studies in the restaurant field was analyzed and discussed. Findings: According to this study, most forecasting studies have focused on model building and its accuracy. These studies used combined and hybrid models more frequently than single qualitative or quantitative models and focused on sales volume. By calculating citation counts and average citation times per year, this study ranked articles published to show their impact on the body of knowledge in this field. In addition, by reviewing the affiliations of the first authors of these studies, this paper found that the United States has been publishing the earliest and most papers related to forecasting in the restaurant industry. Research limitations/implications: This study used the citation count to measure the impact of a study. While this serves the purpose of this study, citation counts may not perfectly represent the value and impact of a study. The findings of this study provide a guide post for future studies. Originality/value: This study provides an updated, comprehensive literature review of the overall development, contributions and limitations of forecasting studies in the restaurant field. The researchers can see the subjects and types of research that have already been conducted and which topics remain unexamined.
Keywords: 650; Restaurant industry; Forecasting; Literature review; Contributions; Limitations